4-Benzyl-3-(2-hydroxyphenyl)-1H-1,2,4-triazole-5(4H)-thione - Dege, N; Çetin, A; Cansiz, A; Sekerci, M; Kazaz, C; Dinçer, M; Büyükgüngör, O (Int Union Crystallography, 2004)
In the title molecule, C15H13N3OS, the triazole ring plane forms dihedral angles of 18.99 (7) and 89.35 (7)degrees with the hydroxyphenyl and benzyl substituent ring planes, respectively. In the crystal structure, the molecules exist as centrosymmetric N-H...S hydrogen-bonded dimers, with an N...S distance of 3.287 (2) Angstrom.